Design and Simulation of a Hybrid Optical Antenna on Engineered Silicon-on-Insulator - Kumar, Varun (My University, 2018)
Microwave photonics has emerged as a promising technology for smart and efficient microwave and photonic networks. Smart antennas together with their counterpart photonic devices are crucial for the realization of microwave photonic systems. In this work, novel design of a hybrid optical antenna containing coupling waveguide, photodetector and an engineered patch antenna is proposed to realize a microwave photonic system. The detailed analysis of the whole hybrid device is presented. An efficient coupling of optical modulated signal on this hybrid chip (antenna) with ultra-low transmission losses at narrow-core waveguide is achieved to obtain high performance photodetection and optimized radiation from an engineered antenna. Firstly, an efficient broadband in-coupler on engineered Siliconon-Insulator (SOI) for strong coupling of optical modulated signal and hybrid chip is designed and analyzed using grating based photonic coupler approach. High-index contrast grating (HCG) is one of the innovative form of grating which is used for this coupling scheme. The formation of high-index contrast grating (HCG) by the periodic layers of silicon and air on top layer of silicon of SOI allows a tight interaction between the guided mode and the grating thereby efficient coupling is achieved by optimizing the different grating parameters i.e. grating thickness (tg), grating period (Λ) and duty cycle (C)over a broad range of wavelength (λ). Further, a new plan for ultra low-loss transmission of this efficient coupled light through HCG assisted narrow-core optical waveguide structure is proposed. The analysis of transmission of guided modes within narrow-core waveguide is done by Finite-difference-time-domain (FDTD) numerical method. An ultra low transmission loss through proposed design is achieved in the narrow-core hollow waveguide due to unique polarization and angular dependence of the HCG reflection spectrum. Finally, HCG assisted hollow waveguide considerably reduces the dispersion and nonlinear effects in datatransmission, and it is insensitive to temperature variations. With all these attractivecharacteristics, the grating based hollow waveguide can be aperfect applicant for on-chip optical communication, compact low loss optical delay lines, and interferometric sensors. Now, an innovative design for hybrid integration of HCG embedded narrow-core waveguide in engineered SOI for efficient photo detection is proposed. A high performance photo detection is realized by integrating of PIN photo detection layer within HCG-assisted narrow-core hollow waveguide. The proposed design demonstrates a good performance device for generating relatively large power at terahertz (THz) frequencies with sufficiently high responsivity and quantum efficiency which is possible because of the presence of surface modes within HCG which get coupled in the photodetection layer leading to a strong optical confinement in that layer. High reflectivity, small penetration length and coupling of lateral surface modes in HCG make it possible to offer improved waveguiding thereby increases the transmitted power. Further, a direct integration of compact terahertz patch antenna with high performance photo detector on engineered SOI is proposed. It is revealed that the multi-resonance of terahertz rays in a copper patch on SOI can be successfully controlled with HCG on the patch. The proposed antenna is shown to work for thirteen frequency bands with suitably low return losses in THz region. The HCG enabled guiding of terahertz rays make it feasible to offer a compact design with an improvement in the antenna characteristics in the form of antenna-gain (G), antenna directivity (D) and radiation efficiency (η) on a compact platform which is feasible since the improved interaction of electromagnetic (EM) fields with the copper patch. All integrated high performance compact optoelectronic devices demonstrate the effectiveness and usefulness of the concept of the photonic feeding antenna and its potential applications to the real radio over-fiber system. This hybrid chip provides a good solution for the future photonic and microwave wireless communication system. This on chip integration of these compact devices may also find applications in sensing and in future microwave/millimetre wave wireless communication system based on photonic networks.
Keywords: High-index Contrast Grating; Terahertz Antenna; Photodetector; Hollow waveguide